Designing an Internet of Things Based Automatic Clothesline - Irvan A. Salihi; Stephan Adriansyah Hulukati; Steven Humena (Fakultas Teknik Universitas Sam Ratulangi, 2019)
In Indonesia, there are 2 seasons, rainy season and dry season. The rainy season occurs from November to March, while the dry season occurs from April to October. With the changing seasons that are very unpredictable, so that the weather cannot be regulated by humans so that it requires the latest technology in this case the internet of things, that concern increases when outside the home and at that time there is no one at home. for fear of clothes that are dried wet with rain water as a result also if clothes that have been dried in the sun and will be exposed to rain water do not rule out the clothes we use will cause a bad odor. By using the mcu node esp 8266 dried is controlled by using a smartphone so that it can be controlled with a long distance then add a rain sensor to anticipate sudden rain fall. If a rain sensor is detected by water, the web system of the relay component will be active and give a command to Nodemcu esp8266, after the program runs the relay will be active and the motor can run forward or backward if the relay is on and the Relay is Off then the motor unable to work forward or backward. Fabric weight is measured by a scale so that it can calculate the weight of the wet cloth obtained. The maximum number of fabrics to be used in this automatic clothesline is to keep the motor running and the motor won't be damaged easily.